Under Western Eyes as an Illustration of the Consequences of Loneliness - Tekşen Memiş, Ayşe (Journal of History Culture and Art Research, 2016)
Abstract The protagonist in Joseph Conrad’s novel Under Western Eyes, Razumov is a man who suffers from loneliness. Although, at first, he was a man who possessed the advantages of youth, education and health to make his life fruitful and enjoyable, he could not escape from being a victim of his own wrong doings that can be said to have happened due to his lacking in sharpness and decisiveness. When he ceases his agonizing fear to confront himself and his own wrong doings, he realizes that he is a shameful person. Together with shame, there comes punishment, which is justified by Razumov himself. Being aware of the fact that he can become neither Ziemianitch nor Haldin, he finally internalizes the idea of being “no one” as pointed out by Miss Haldin at the end of the novel. As suggested by Miss Haldin, all humans will be pitied, in the end, no matter which ideology they come from. In this sense, being “no one” serves as a good enough categorization for Razumov who looked for a place for himself in life; at the beginning of the novel, through material success and, in the second half of the novel, through feelings. Razumov is the representation of an ordinary man who is in search of a place for himself and who has his own agitations driven from past experiences. In a world that is described through the binaries of the good and bad, he is the representation of the man who stands alone without a strong adherence to a point of view in life and will end up being categorized as “no one”.